A family-focused oral-health toy library: towards a new direction in oral health education - González-Ariza, Sandra; Giraldo, María Cristina; Varela, Janneth; Peña, Elisa María; Giraldo, Juan Pablo; Orozco, Jorge Jhovanny (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: discovering strategies to promote motivation of personal skills must be a permanent task of oral health professionals. The purpose of this program was to create a place, within the toy library, devoted to strengthening oral health habits, with theguidance of trained personnel such as toy librarians and dentists, who developed ludic strategies for teaching and reinforcing oral health knowledge among children and their families. Methods: this was a pre-experimental community intervention program, which evaluated 99 children between 4 and 12 years of age. Surveys were conducted in order to assess the students’, parents’, and guardians’ knowledge before and after their interaction with the ludic material; also, caries and dental plaque indexes were measured. Results: this training program allowed improving the knowledge level among parents and children by 21 and 29% respectively. The average percentage of dental plaque was 38.2 ± 18.9 showing a difference of 18.3% with respect to the initi l exam. Among the surfaces with caries history, those which had been restored were predominant (1.5 ± 2.6). The qualitative analysis of the children’s perception of the games revealed that they found them positive, nice, fun, and educational. Conclusions: establishing an oral health toy library, as a constructive environment that involves innovative strategies aimed at health education, allowed socialization of the studied population as well as promotion of healthy oral habits and reinforcement of self-care among this population.